Structural equation modelling analysis on relationships of job demands and resources with work engagement, burnout and work ability: an observational study among physicians in Dutch hospitals - Renée Scheepers; Milou Silkens; Kiki Lombarts; Maarten Debets (BMJ Open)
Objective To investigate to what extent work engagement mediates the relationships of job resources with work ability, and to what extent burnout mediates the relationships of job demands and resources with work ability.Design Multicentre observational study.Setting Academic and non-academic hospitals in the Netherlands.Participants Physicians (n=385) participated in this study.Primary and secondary outcome measures We measured work ability with selected items from the validated Questionnaire of Experience and Evaluation of Work 2.0 (QEEW V.2.0), work engagement with the Utrecht Work Engagement Scale and burnout with the exhaustion subscale of the Oldenburg Burnout Inventory. The job demand ‘workload’ and job resources ‘development opportunities’, ‘participation in decision-making’, ‘inspirational leadership’ and ‘relationships with colleagues’ were measured using the QEEW V.2.0. The job demand ‘bureaucratic burden’ was measured with the Three Item Red Tape scale. A structural equation model was built to answer our research question.Results Work engagement mediated relationships of job resources with physicians’ work ability, and burnout mediated relationships of job resources and demands with work ability. Development opportunities (β=0.39, SE=0.12, p<0.001), participation in decision-making (β=0.18, SE=0.08, p=0.028) and relationships with colleagues (β=0.19, SE=0.19, p=0.002) were positively related to work engagement. Development opportunities (β=−0.20, SE=0.08, p=0.004) were negatively related and workload (β=0.51, SE=0.19, p<0.001) was positively related to burnout. Work engagement (β=0.22, SE=0.04, p<0.001) was positively related and burnout (β=−0.56, SE=0.06, p<0.001) was negatively related to work ability.Conclusions Physicians’ work engagement and burnout mediated the relationships of various job demands and resources with their work ability. More work-engaged and less burned-out physicians reported better work ability. Hospitals may attenuate excessive workloads and facilitate development opportunities, participation in decision-making and good collegial relationships to enhance physicians’ occupational well-being and performance.